Mechanisms underlying the reversal of hypoxia-induced energy metabolic reprogramming in cardiomyocytes by Poria cocos triterpenoids: integrated regulation of mitochondrial dynamics and the autophagy–lysosomal pathway - Zuoyue Wu; Jiadan Liao; Huilei Xu; Hongwei Hou; Jia Song (Frontiers in Cardiovascular Medicine, 2026)
Objective To elucidate the mechanisms by which Poria cocos triterpenoids reverse hypoxia-induced energy metabolic reprogramming in cardiomyocytes through integrated regulation of mitochondrial dynamics and the autophagy–lysosomal pathway. Methods A hypoxic injury model was established in H9c2 rat cardiomyoblasts. Cells were randomized into five groups: normal control, hypoxia model, and low-, medium-, and high-dose Poria cocos triterpenoid–treated groups. Cell viability was assessed using the Cell Counting Kit-8 (CCK-8) assay. Western blotting quantified protein expression levels of mitochondrial fusion (Mfn1, Mfn2, OPA1) and fission (Drp1, Fis1) regulators; autophagy–lysosomal markers (LC3-II/I ratio, p62, PINK1, Parkin, LAMP1, ATG5); and key metabolic enzymes (CPT1, PFK-2). Mitochondrial respiratory control ratio (RCR) and ATP production rate were measured via high-resolution respirometry; extracellular acidification rate (ECAR), oxygen consumption rate (OCR), and fatty acid oxidation (FAO) efficiency were determined using Seahorse XF Analyzer. Intracellular lactate and pyruvate concentrations were quantified enzymatically. Functional validation employed siRNA-mediated knockdown of Drp1 or ATG5 to assess mechanistic dependency. Results Compared with the normal control group, the hypoxia model group exhibited significantly reduced cell viability ( P < 0.05), impaired mitochondrial fusion (downregulated Mfn1, Mfn2, OPA1) and enhanced fission ( P < 0.05). Mitochondrial bioenergetics were compromised: RCR, ATP production rate, OCR, FAO efficiency, CPT1 activity, and pyruvate levels decreased ( P < 0.05), whereas lactate accumulation, ECAR, and PFK-2 activity increased ( P < 0.05), indicating a glycolytic shift. Autophagy–lysosomal flux was suppressed: LC3-II/I ratio, PINK1, Parkin, and LAMP1 expression declined, while p62 accumulated ( P < 0.05). Treatment with Poria cocos triterpenoids dose-dependently reversed these alterations: viability improved; fusion proteins increased and fission proteins decreased ( P < 0.05); mitochondrial respiration, ATP synthesis, FAO efficiency, and pyruvate levels recovered; glycolytic parameters normalized; and autophagic flux was restored (elevated LC3-II/I, PINK1, Parkin, LAMP1; reduced p62, with maximal effects observed at the high dose ( P < 0.05). Mechanistic validation confirmed that Drp1 knockdown synergistically enhanced the protective effects of triterpenoids—further improving OCR, ATP production, FAO efficiency, and CPT1 activity while suppressing ECAR, lactate, and PFK-2 activity ( P < 0.05). In contrast, ATG5 knockdown abolished triterpenoid-mediated rescue of viability, bioenergetics, and metabolic phenotype ( P < 0.05), confirming ATG5-dependent autophagy as essential for the therapeutic effect. Conclusion Poria cocos triterpenoids restore energy homeostasis in hypoxic cardiomyocytes by concurrently normalizing Drp1-mediated mitochondrial fission and ATG5-dependent autophagic clearance. This dual regulation rescues mitochondrial structural integrity, enhances oxidative phosphorylation, suppresses pathological glycolysis, and thereby reverses hypoxia-induced metabolic reprogramming—ultimately preserving cardiomyocyte viability.